2019
DOI: 10.1177/1053815119847235
|View full text |Cite
|
Sign up to set email alerts
|

Needs of Military Families: Family and Educator Perspective

Abstract: Limited research has focused on the unique needs of military families and their preschool-age children and even less work focused on military families whose preschool children have special needs or disabilities. Researchers implemented a multicase qualitative research design conducted at two sites to gain the perspectives across all service ranks. The study included two groups of participants from each site including (a) early educators working for the school district associated with each military base, and (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Rech et al (2021) explored the use and perceptions of the NAEYC family engagement principles among early childhood educators in addition to barriers to implementation. Classen et al (2019) identified barriers and facilitators between military families and early childhood educators when collaborating to meet the needs of young children with disabilities. Using interview questions aligned with the DEC Recommended Practices, the study found that families viewed educators who encouraged collaborative partnerships as showing empathy, communicating often, and exhibiting professionalism.…”
Section: Parent and Educator Family Engagement Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rech et al (2021) explored the use and perceptions of the NAEYC family engagement principles among early childhood educators in addition to barriers to implementation. Classen et al (2019) identified barriers and facilitators between military families and early childhood educators when collaborating to meet the needs of young children with disabilities. Using interview questions aligned with the DEC Recommended Practices, the study found that families viewed educators who encouraged collaborative partnerships as showing empathy, communicating often, and exhibiting professionalism.…”
Section: Parent and Educator Family Engagement Experiencesmentioning
confidence: 99%
“…Using interview questions aligned with the DEC Recommended Practices, the study found that families viewed educators who encouraged collaborative partnerships as showing empathy, communicating often, and exhibiting professionalism. Practices such as communication and parent-educator partnerships were important to parents and educators (Classen et al, 2019). Macy et al (2019) stated that positive, trusting relationships can ensure effective two-way communication.…”
Section: Parent and Educator Family Engagement Experiencesmentioning
confidence: 99%
“…It is not an easy thing to apply the values or norms above while still providing a comfortable feeling for students because it is possible to apply these norms to be indoctrination. The view of semi-military schools among students today indicates the need to change such perceptions to attract more students to achieve a more diverse future dream destination (Classen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Together, these data suggest that there may be nearly 74,077 children under the age of 15 in active duty military families who had diagnosed disabilities in 2016, of which a large percentage may be accessing EI and special education services through local education agencies. Therefore, in the United States, in communities both near and far from military installations, professionals are likely to encounter and serve one or more military families with children with disabilities in inclusive EC programs during their career (Classen, 2014).…”
mentioning
confidence: 99%
“…Researchers have long asserted the importance of professionals developing critical knowledge and skills when working with children and families from backgrounds different from their own (Lynch & Hanson, 2011). While there is much more to learn about the diverse children and families served in EC programs, little has been written about military families in the EC literature and, in particular, in the early intervention (EI) and early childhood special education (ECSE) literature (Classen, 2014; Hile, Weglarz-Ward, DiPietro-Wells, Santos, & Ostrosky, 2017; Murphey, Darling-Churchill, & Chrisler, 2011). For the purpose of this article, we use the phrase military families to include families of children with and without disabilities where one or both parents are active military service personnel.…”
mentioning
confidence: 99%